2023
DOI: 10.1002/gj.4773
|View full text |Cite
|
Sign up to set email alerts
|

Ti‐in‐zircon and Ti‐in‐quartz thermometry using electron probe microanalysis: A promising approach in retrieving thermal conditions of granulite facies metamorphism and felsic magmatism in the Sandmata Complex, Aravalli Craton (NW India)

Abstract: The titanium (Ti) concentrations in zircon and quartz and corresponding thermometers have been regarded as powerful monitors that constrain petrogenetically meaningful temperature conditions of crystallization and metamorphism. The precise measurement of trace elements by electron probe microanalyzer (EPMA) is quite challenging as their x‐ray intensities are only slightly higher than the Bremsstrahlung background, leading to significant errors while quantifying the elemental abundances (e.g., Ti‐in‐zircon). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 134 publications
(297 reference statements)
0
1
0
Order By: Relevance
“…Applying this method to USGS reference glasses revealed that USGS BHVO-2G (basalt) had the highest degree of homogeneity for both Cl and F in geological samples. Ghosh et al 252 reported an EPMA method to determine Ti concentrations in zircon and quartz to retrieve thermal conditions of metamorphism and magmatism by Ti-in-zircon and Ti-in-quartz thermometry. To meet the challenges posed by X-ray intensities being only slightly above Bremsstrahlung background when measuring trace elements, this method combined long counting times at peak and background positions, simultaneous acquisition of Ti in three spectrometers and processing of data using the sub-counting method in which the total analytical time was split into smaller cycles to reduce any effects from surface damage on the final counts.…”
Section: Analysis Of Geological Materialsmentioning
confidence: 99%
“…Applying this method to USGS reference glasses revealed that USGS BHVO-2G (basalt) had the highest degree of homogeneity for both Cl and F in geological samples. Ghosh et al 252 reported an EPMA method to determine Ti concentrations in zircon and quartz to retrieve thermal conditions of metamorphism and magmatism by Ti-in-zircon and Ti-in-quartz thermometry. To meet the challenges posed by X-ray intensities being only slightly above Bremsstrahlung background when measuring trace elements, this method combined long counting times at peak and background positions, simultaneous acquisition of Ti in three spectrometers and processing of data using the sub-counting method in which the total analytical time was split into smaller cycles to reduce any effects from surface damage on the final counts.…”
Section: Analysis Of Geological Materialsmentioning
confidence: 99%